2023
DOI: 10.3389/fpsyg.2023.1073995
|View full text |Cite
|
Sign up to set email alerts
|

Symptom distress and suicidal ideation among Chinese ovarian cancer patients: A moderated mediation model of depression and suicide resilience

Abstract: ObjectiveThe aim of this study was to examine whether depression mediates the relationship between symptom distress and suicidal ideation in Chinese patients with ovarian cancer, and whether this mediating effect was moderated by suicide resilience.MethodsFrom March to October 2022, this cross-sectional study was performed in a three Grade 3A hospital and an oncology specialty hospital in Wuhan, Hubei Province, China. Ultimately, 213 ovarian cancer patients completed anonymous self-report. Bootstrapping method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Consistent with previous studies, physical symptoms and psychological distress predicted an increased likelihood of SI among patients with advanced cancer. 28 , 29 Previous research suggested that quality of life could act as a mediator in the association between symptom burden and SI, 4 and thus active symptom control, for example, analgesia, to improve the overall life quality should be essential to reduce SI. From the nomogram, anxiety and depression contributed the most to the model, which underlined the important role of anxiety/depression in the formation of SI.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, physical symptoms and psychological distress predicted an increased likelihood of SI among patients with advanced cancer. 28 , 29 Previous research suggested that quality of life could act as a mediator in the association between symptom burden and SI, 4 and thus active symptom control, for example, analgesia, to improve the overall life quality should be essential to reduce SI. From the nomogram, anxiety and depression contributed the most to the model, which underlined the important role of anxiety/depression in the formation of SI.…”
Section: Discussionmentioning
confidence: 99%